Teknik Self-Management untuk Menurunkan Perilaku Membolos pada Siswa Kelas XI - Eriska Rahma; Citrawanti Oktavia; Ima Fitri Sholichah (Jurnal Psikoedukasi dan Konseling, 2022)
This study aims to determine the effect of self-management techniques on students' behaviour. This research was carried out on class XI students in Islamic high school. This study uses one pretest-posttest design group without comparison groups or control groups, the population employed by class XI IA. A total of 5 students obtained as many as four students. Sampling using a purposive sampling technique. Data collection methods use trooting behaviour questionnaires. Data analysis techniques use parametric paired sample t-test analysis. The results of the study. It shows that self-management techniques reduce the behaviour of skipping students. This is evidenced by the difference in lowering behaviour of diving between the pre-test and post-test results, where the average post-test results are lower than the pre-test results after a self-management technique is given. Based on the results of the pre-test and the existing post-test showed a change in the behaviour. Who experienced a decrease in the conduct of skipping after individual counselling using the behaviour approach with self-management techniques